DESIGNING CANCER GROUPS FOR MAXIMUM EFFECTIVENESS - Daste, Barry M (Groupwork, 2020)
This article attempts to shed light on some of the problems involved in developing optimum service groups for cancer patients and offers ideas concerning the design, content, leadership and membership of these groups. The article begins with a literature review of current research on issues faced by cancer patients and how these have been handled in support groups and therapy groups across the country. Following this, suggestions are offered to assist those involved in planning for these groups to deal with some of the potential difficulties encountered by many of these groups. Interest in this project grew out of the author’s personal experience with cancer and from the experience of being first a participant, and later a leader, in groups for cancer patients. Publisher’s note: We are now putting all back issues of Groupwork on line. Articles in this issue have been scanned to pdf files as viable original typesetting files no longer exist. Though they may not look it, these files are to some extent searchable. This issue was published nearly 30 years ago. We have stated author professional details as received at time of publication.